Relación de Calidad de Vida y Condición de Empleo o Desempleo en Adultos Mayores de 60 Años, Ubicados en la Localidad Rafael Uribe Uribe de la Ciudad de Bogotá (2022)
This study describes the relationship between the quality of life and the employment or unemployment situation of adults over 60 years old, located in Rafael Uribe Uribe locality in Bogotá. Through the implementation of the instruments related to quality of life and employment or unemployment situation in adults over 60 years old, in addition to the Rosenberg test to measure self-esteem and the QLI-Sp quality of life questionnaire. There was a sample of 31 elderly people, to identify if there are variables regarding the employability situation that is related to quality of life